2023
DOI: 10.21511/bbs.18(1).2023.01
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the asymmetry of religiosity-based loyalty of Islamic bank depositors

Abstract: Religiosity is one of many essential aspects that stands as the motivation of people’s behaviour. Its importance expands to the field of banking, especially Islamic banks that take Islamic teaching as their backbone. This study aimed to seek religiosity motivation among Islamic bank depositors by exploring the possible asymmetric effect of interest rates on the type of deposits. By using the NARDL approach, this study investigates the relationship between the conventional deposit interest rate on the type of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Most of the studies found that CSR disclosure has an impact on the earnings and profitability of companies, including Islamic banks (Setiawati et al, 2022;Yuliartanti & Handayani, 2023). Apart from it, Athief & Ma'ruf (2023) found that Indonesian Islamic banks' depositors and not influenced by the raising of interest rates and are religiously loyal. This means that Islamic banks customers believe in good things done by Islamic banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the studies found that CSR disclosure has an impact on the earnings and profitability of companies, including Islamic banks (Setiawati et al, 2022;Yuliartanti & Handayani, 2023). Apart from it, Athief & Ma'ruf (2023) found that Indonesian Islamic banks' depositors and not influenced by the raising of interest rates and are religiously loyal. This means that Islamic banks customers believe in good things done by Islamic banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presence of Islamic banking is a complement to the existing conventional banking system (Athief & Ma'ruf, 2023). Entering the era of the industrial revolution 4.0, the politics of developing Islamic banking law must take on a role to prevent the law from becoming an obstacle in-state activities, so one way that can be done as an effective and efficient form of action is through optimizing information technology in the field of Islamic banking (Syamsuddin & Diarti, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…
generally Islamic banks depositors are religiously loyal (Athief & Ma'ruf, 2023). A compelling picture of the organization of a company can be seen if it has economic, social, and environmental aspects (Kamela & Alam, 2021).
…”
mentioning
confidence: 99%